IMPROVING STUDENTS’ SPEAKING SKILL THROUGH ENGLISH MOVIE IN SCOPE OF SPEAKING FOR GENERAL COMMUNICATION - Aseptiana Parmawati; Ratih Inayah (Eltin Journal : Journal of English Language Teaching in Indonesia, 2019)
Speaking for general communication is compulsory subject that must be taken by students during second semester. In reality, most of the students at IKIP Siliwangi face some problems related to speaking skill. To improve the students’ speaking skill, the lecturers need to know what media is the most suitable for the students. This research used Collaborative Classroom Action Research (CAR). The objectives of the study are: 1) finding out whether or not English Movie can improve the students’ speaking skill 2) finding out classroom situation when English Movie implemented in speaking class. To collect data, the researcher used instruments of observations, tests and questionnaires. The finding showed that the use of English Movie was effective in improving the speaking abilities of the student in class. This can be seen from the improvements after each cycle. The average score of pre test was 70.5. After the implementation of English Movie in every cycle, the students’ speaking score were getting better. It can be seen from the result of students’ average score 76.5 in cycle 1 and 81 in cycle 2. Therefore, it can be concluded that English Movie can improve students’ speaking skill and improve speaking classroom into a better situation.Keywords: Improving, Speaking, English Movie